Positive airway pressure devices for the management of breathlessness. Issue 3 (September 2018) - D'Cruz, Rebecca F.; Kaltsakas, Georgios; Suh, Eui-Sik; Murphy, Patrick B.; Hart, Nicholas
Abstract : Purpose of review: Breathlessness is a common symptom in many chronic diseases and may be refractory to pharmacotherapy. In this review, we discuss the pathophysiology of breathlessness and the role of positive airway pressure (PAP) devices to ameliorate it. Recent findings: Breathlessness is directly related to neural respiratory drive, which can be modified by addressing the imbalance between respiratory muscle load and capacity. Noninvasive PAP devices have been applied to patients limited by exertional breathless and, as the disease progresses, breathlessness at rest. The application of PAP is focussed on addressing the imbalance in load and capacity, aiming to reduce neural respiratory drive and breathlessness. Indeed, noninvasive bi-level PAP devices have been employed to enhance exercise capacity by enhancing pulmonary mechanics and reduce neural drive in chronic obstructive pulmonary disease (COPD) patients, and reduce breathlessness for patients with progressive neuromuscular disease (NMD) by enhancing respiratory muscle capacity. Novel continuous PAP devices have been used to maintain central airways patency in patients with excessive dynamic airway collapse (EDAC) and target expiratory flow limitation in severe COPD. Summary: PAP devices can reduce exertional and resting breathlessness by reducing the load on the system and enhancing capacity to reduce neural respiratory drive.